Decisions for war, 1914-1917 - Hamilton, Richard F.; Herwig, Holger H. (Cambridge University Press, 2005)
"This work poses an easy but perplexing question about World War I - Why did it happen? Several of the oft-cited causes are reviewed and discussed. The argument of the alliance systems is inadequate, most agreements lacking compelling force. The argument of an accident (or "slide") is also inadequate, given the clear and unambiguous evidence of intentions. The arguments of mass demands - those focusing on nationalism, militarism, and social Darwinism - it is argued, are insufficient, lacking indications of frequency, intensity, and process (how they influenced the various decisions). Decisions for War focuses on the choices made by small coteries, in Austria-Hungary, Germany, Russia, France, Britain, and elsewhere."--Jacket